RELIGIOUS CONNECTIONS BETWEEN THE OTTOMAN EMPIRE AND TURKISTAN (DURING THE XIXth AND EARLY XXth CENTURIES): ISTANBUL AS A PILGRIMAGE ROAD - Baglan Shorayev; Akmaral Ospanova (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi)
The pilgrimage, holds significant religious importance in Islam and serves as a vital factor in the political, economic, and social development of states. It acts as an institutional structure that unites Muslims from diverse cultures and languages. In the 19th century, Hajj was a crucial link between the people of Turkestan, under Tsarist Russia, and the Ottoman Empire. Despite political separations, the pilgrimage maintained relations between the Ottoman Empire and the Turkestan region.This study delves into the history of the Hajj pilgrimage by Kazakh Turks through Ottoman lands, highlighting the religious connections between the Ottoman Empire and Turkestan. The period from the late 19th century to the early 20th century is particularly significant for evaluating the political, diplomatic, and cultural ties between the Ottoman Empire and the Kazakh Turks. During this time, the number of Kazakh pilgrims increased, driven by various factors.The pilgrimage of Kazakh Turks through Ottoman territories raised suspicions in Tsarist Russia, leading to persecution of Ottoman citizens who traded in Kazakh lands and encouraged pilgrimage. This historical analysis draws on data from the Kazakhstan Central Archive, providing insights into the pilgrimage routes and the support offered by the Ottoman Sultan to Turkestan pilgrims.The article covers multiple aspects: the religious ties between the Ottoman Empire and Turkestan, Tsarist Russia's laws on pilgrimage, pilgrimage routes, Turkestan lodges in Istanbul, contributions to the Hejaz Railway's construction, and the Ottoman Sultan's aid to Turkestan pilgrims. Additionally, it explores Tsarist Russia's smear campaigns against Ottoman Turks in Kazakhstan, the impact of Russian expansion in the 19th century, and the political significance of the Hejaz Railway for ensuring pilgrimage safety.The study relies on documents from the Kazakhstan Archive, systematically scanned and categorized by subject, to present a comprehensive view of these historical events and their implications.